1986
DOI: 10.1113/expphysiol.1986.sp002995
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Energy Metabolism in the New‐born Infant, Piglet and Lamb

Abstract: Characteristics of energy metabolism in the new‐born infant, piglet and lamb have been compared quantitatively in order to assess how the constraints imposed by the availabilities of energy substrates in body reserves and colostrum differ between species and affect the new‐born's well being during the first day after birth. Three air temperature ranges, described as thermoneutral (32‐38 °C), moderate (18‐26 °C) and cold (0‐10 °C) and representing the usual birth environments of infants, piglets and lambs, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(102 citation statements)
references
References 62 publications
0
101
1
Order By: Relevance
“…A decrease in plasma glucose contrasts with the response observed over the first few hours of life in starved calves (Jeffrey & Read, 1981) which are more dependent on glucose production from the mobilisation of endogenous energy glycogen stores than on nutrients obtained orally (Mellor & Cockburn, 1986). In the present study it is likely that hypoxia resulted in a reduction in hepatic gluconeogenesis following a fall in both gastrointestinal tract and hepatic portal blood flow (Sidi et al 1983b).…”
Section: Statistical Analysescontrasting
confidence: 49%
“…A decrease in plasma glucose contrasts with the response observed over the first few hours of life in starved calves (Jeffrey & Read, 1981) which are more dependent on glucose production from the mobilisation of endogenous energy glycogen stores than on nutrients obtained orally (Mellor & Cockburn, 1986). In the present study it is likely that hypoxia resulted in a reduction in hepatic gluconeogenesis following a fall in both gastrointestinal tract and hepatic portal blood flow (Sidi et al 1983b).…”
Section: Statistical Analysescontrasting
confidence: 49%
“…Early ingestion of colostrum has an additional benefit in that it increases heat production by 17% even if body energy reserves are still replete, enhancing resistance to hypothermia. Under optimal conditions, neonates would consume sufficient Dwyer, Conington, Corbiere, Holmøy, Muri, Nowak, Rooke, Vipond and Gautier colostrum to meet their carbohydrate requirement for 14 h of the first 24 h of life (Mellor and Cockburn, 1986). Utilisation of glycogen is therefore essential to make up the difference, and lambs face the first few days with largely depleted liver and muscle glycogen.…”
Section: Biological Factors Involved In Lamb and Kid Mortality/survivalmentioning
confidence: 99%
“…McCance and Alexander (1959) calculated that the heat produced by a 3.5 kg fasted lamb under field conditions is 0.19 MJ/h, which equates to about 30 ml/colostrum. On this basis, a new-born lamb requires between 180 and 290 ml of colostrum/kg BW during the first 18 h after birth (Shubber et al, 1979;Mellor and Cockburn, 1986;Mellor and Murray, 1986;Mellor, 1988), on top of an immediate requirement at birth of 50 ml/kg BW to avoid hypothermia (Robinson et al, 2002). Pattinson et al (1995) suggested that the weight of colostrum required by a lamb varies from 140 to 175 g/kg of birth weight during the first 24 h of life for lambs born indoors at temperatures between 2°C and 10°C.…”
Section: Colostrum Requirements Of the New-born Lambmentioning
confidence: 99%